Enhancement in free-tropospheric aerosol loading over India. (1st May 2022) - Prijith, S.S.; Sai, M.V.R. Sesha
Abstract: Free-tropospheric aerosol loading and its changes assume importance as the diabatic heating due to radiation absorption by aerosols is more intense at higher altitudes. The present study quantifies trends in free-tropospheric aerosol loading over Indian landmass and examines the role of local production and long range transport, using multi-satellite observations and reanalysis data. Increasing trends in free-tropospheric aerosol abundance are seen over most of the regions in almost all the seasons. Strongest positive trend over the Indian landmass is seen in post-monsoon, with mean rate of increase in free-tropospheric aerosol optical depth (AODFree Troposphere ) 0.063dec −1 . While dust aerosol loading in the free-troposphere decreases, smoke aerosol concentration increases over the Indian landmass. While increase in columnar and free-tropospheric aerosol loading is seen over larger regions of the Indian landmass, including regions of northwest India, Indo Gangetic Plain (IGP), central India and southern peninsula, enhancement in aerosol production is observed mainly over the regions of northwest India in post-monsoon. Due to the prevailing westerly winds, aerosols over northwest India are transported through IGP to its central and eastern regions. Increase in aerosol production over northwest India and strengthening of updrafts over the central and eastern IGP lead to vertical uplift of more aerosols into the free-tropospheric altitudes. These free-tropospheric aerosols are subsequently transported, by the prevailing anti-cyclonic system, to the regions of central India and southern peninsula and cause the enhancement in free-tropospheric aerosol loading over these regions in post-monsoon. Though strengthening of updraft is observed over the regions of central India and southern Peninsula, net aerosol production is not seen to be increasing over these regions. The observed enhancement in free-tropospheric aerosols over Indian landmass is important as they can affect the thermal structure and stability of the atmosphere and modify the properties and distribution of clouds. Highlights: Increasing trends in free-tropospheric aerosols over Indian land mass. Strongest positive trend (0.063dec −1 ) of free-troposphere aerosols in post-monsoon. While dust loading decreases, smoke aerosol concentration increases in free-troposphere. Increase in aerosol production over Northwest India in post-monsoon. Changes in circulation cause spread of aerosols in the free-troposphere over large regions.